The political economy of rural-urban conflict predation, production, and peripheries - McDougal, Topher L. (Oxford University Press, 2017)
Why do some rebel insurgencies target cities as economic prey, whilst others are content to trade with them? This volume examines how the trade networks underpinning the economic relationship between rural and urban areas differ in their impact on (and response to) the combat frontier.